2000
DOI: 10.1002/1097-0215(20001001)88:1<21::aid-ijc4>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Expression of emmprin (CD147), a cell surface inducer of matrix metalloproteinases, in normal human brain and gliomas

Abstract: EMMPRIN (extracellular matrix metalloproteinase inducer), also called CD147, basigin or M6 in the human, is a member of the immunoglobulin superfamily that is present on the surface of tumor cells and stimulates adjacent fibroblasts to produce matrix metalloproteinases (MMPs). In our study, we investigated expression of EMMPRIN in human normal brain and gliomas, since mouse basigin and chicken HT7, the species homologues of human EMMPRIN, are associated with neuronal interactions and normal blood‐brain barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
91
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(102 citation statements)
references
References 38 publications
9
91
0
2
Order By: Relevance
“…EMM-PRIN expression also was reported to be significantly elevated in gliomas compared to normal brain tissue. 33 Consistent with our observations, glioblastoma multiforme displayed the highest level of EMMPRIN expression. Expression of EMMPRIN antisense RNA has been shown to result in decreased migration and invasion of glioblastoma cells.…”
Section: Discussionsupporting
confidence: 88%
“…EMM-PRIN expression also was reported to be significantly elevated in gliomas compared to normal brain tissue. 33 Consistent with our observations, glioblastoma multiforme displayed the highest level of EMMPRIN expression. Expression of EMMPRIN antisense RNA has been shown to result in decreased migration and invasion of glioblastoma cells.…”
Section: Discussionsupporting
confidence: 88%
“…6 Previous studies have shown that CD147 is highly expressed in melanoma and glioma cells, and induces tumor invasion by stimulating generation of MMPs by adjacent fibroblast cells or other stromal cells. 14,15 Although normal cells also express CD147, it seems that CD147 is highly expressed in many human cancer cells, 26 -30 and the tumor-specific induction of MMPs in facilitating tumor invasion and metastasis caused by CD147 may be due to different glycosylation or modification of CD147 molecules in tumor cells as compared with the normal cells. 6 Transfection of CD147 cDNA into slow-growing breast cancer cells in vivo turned them into more tumorigenic and invasive cancer cells as compared with the mock transfected cells.…”
Section: Discussionmentioning
confidence: 99%
“…6,[11][12][13] Studies have shown that CypA binds to CD147 and transmits a signal to downstream cascades. CD147 is found to be highly expressed in human gliomas as compared with nonneoplastic brain tissues, 14 and is expressed on melanoma cells and induces tumor cell invasion by stimulating production of matrix metalloproteinases (MMPs) by adjacent fibroblasts, resulting in tumor invasion and metastasis. 15 However, the roles of CD147 in pancreatic cancer growth are not clear.…”
mentioning
confidence: 99%
“…CD147 expression is elevated on several human tumors and has been correlated with the malignancy in some cancers such as primary breast cancer and ovarian cancer, etc. (7)(8)(9)(10)(11)(12). Despite the close correlation between CD147 expression and malignancy of some tumors, it is not clear whether CD147 has a functional role in tumor genesis and hepatocellular carcinoma (HCC) progression.…”
Section: Introductionmentioning
confidence: 99%